Improving the Process of Separating Row Cotton from Air in Order to Preserve its Natural Properties - Eshmurodov Dilmurod Dusmurod o’g’li; Davlatova Zuxra Shuxratovna; Xashimova Nilufar Olim qizi (Genius Journals, 2022)
The article is devoted to the study of the equipment of a cotton fibers processing plant. At the same time, an improved version of the cotton fibers Separator is recommended. The results of the enhanced separator's experimental results are also presented. The scientific significance of the research results is justified by the development of a separator design ensuring the preservation of the initial quality indicators of cotton by protecting it from mechanical influence, as well as by developing a method for preventing obstruction during separation of cotton from air, by rational arrangement of the air chamber in the separator working chamber, and by increasing the efficiency of the separation process by establishing special guides after the inlet pipe
Keywords: separator; vacuum clever; fiber; raw cotton